EVALUATING THE INFORMATION ABOUT USE OF PHARMACOTHERAPY FROM POPULATION IN SOME DISTRICTS IN SALAHUDDIN GOVERNORATE - Imad Noaman Shareef. (Chelonian Research Foundation, 2023)
The study focused on 90 people (42 in urban areas, 48 ​​in rural areas) from some districts (Tikri, Sherqat, Tuz) from January 2023 to May in Salahuddin Province. The aim of this cross-sectional study was to evaluate population-based information on the use of pharmacotherapy. The paper survey provided important information on the use of drug therapy in urban and rural area. These paper questionnaire include:- - Do you go to the doctor when you don't feel well? - Are the treatments carried out as prescribed by a doctor? - Is the treatment carried out according to the doctor's instructions? - Were the medications taken on time? – Is the medicine taken during or after meals? – How do I store medication at home? – Which types of treatment should be preferred? - If a treatment is not completed, will it be given to another patient at home? - Do you pay attention to the expiry date when buying medication? – If you forget to take the medicine on time, will you take it later or not? - If your children get different diseases at the same time, do you treat them the same or go to the doctor? – Should I consult a doctor or restart my current medication if I experience symptoms of an illness I previously suffered from? - If a neighbor or friend gives you medication, do you use it or go to the doctor? – Do you wash your hands before treatment? The result of this study in all respects provides important information for the applications of pharmacotherapy. Conclusion: This study provided good information about the use of pharmacotherapy in these districts, but required further information from other population questionnaires. Keyword: population, paper questionnaire (direct interviewer form).